2019
DOI: 10.1016/j.ajem.2018.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Patient and clinician factors associated with prehospital pain treatment and outcomes: cross sectional study

Abstract: There was no association between patient sex or ambulance staff sex or grade and analgesic administration or pain reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 25 publications
0
33
1
Order By: Relevance
“…33,34 In the prehospital setting, data are even scarcer and also reveal inconsistent findings regarding pain management approaches and proper pain relief according to provider gender. 13,[35][36][37] There are several explanations for the discrepancy of findings in literature and discordance with this study. First, most studies in this field were performed in an experimental or hospital/clinic environment.…”
Section: Discussioncontrasting
confidence: 95%
“…33,34 In the prehospital setting, data are even scarcer and also reveal inconsistent findings regarding pain management approaches and proper pain relief according to provider gender. 13,[35][36][37] There are several explanations for the discrepancy of findings in literature and discordance with this study. First, most studies in this field were performed in an experimental or hospital/clinic environment.…”
Section: Discussioncontrasting
confidence: 95%
“…Despite the availability of evidence-based guidelines, pain has been shown to be under assessed and undertreated. (14)(15)(16)(17)(18)(19) Several predictors of disparity in the provision of analgesia by paramedics have been described, including sex and age. (20,21) However, there is scant evidence of the effect of paramedic qualification level on analgesic administration in a setting where paramedics at all levels of qualification can provide pharmacological management of pain.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the majority of patients reporting moderate to severe pain received analgesia, and this is in contrast with other studies that show frequency of analgesia administration by paramedics. (16,19,22) This may reflect the importance placed on the assessment and early management of pain by the ambulance service and/or the clinical capabilities of paramedics employed by this agency. The effect of organizational or cultural influences on pain management may be a useful line on inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine, for example, requires intravenous cannulation and a paramedic to administer; potential side effects may restrict its use (sedation, respiratory depression, nausea, and hypotension). Solutions may include expanding the range of analgesics available, including to non-paramedic staff [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%